2008
DOI: 10.1159/000129658
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Multifaceted Psychiatric Intervention Targeted for the Complex Medically Ill: A Randomized Controlled Trial

Abstract: Background: This study evaluated a multifaceted psychiatric intervention targeted at the complex medically ill identified by means of the INTERMED, an instrument to assess case complexity. Methods: Of 885 rheumatology inpatients and diabetes outpatients who were assessed for eligibility, 247 were identified as complex (INTERMED score >20) and randomized to the intervention (n = 125, 84 rheumatology and 41 diabetes patients) or care as usual (n = 122, 78 rheumatology and 44 diabetes patients). For the majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 101 publications
2
49
0
6
Order By: Relevance
“…(8)(9)(10)(11) The profile of the elderly investigated in this study showed a mean age of 72.3 years, females predominated, with a socioeconomic income in the range of three times the minimum wage, a profile that was similar to that observed in the literature. (12)(13)(14)(15) The increase in longevity was a response to the evolution of medical science, however, the quality of life of the elderly was one of the greatest challenges in developing countries, where poverty and social inequality were highlighted.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…(8)(9)(10)(11) The profile of the elderly investigated in this study showed a mean age of 72.3 years, females predominated, with a socioeconomic income in the range of three times the minimum wage, a profile that was similar to that observed in the literature. (12)(13)(14)(15) The increase in longevity was a response to the evolution of medical science, however, the quality of life of the elderly was one of the greatest challenges in developing countries, where poverty and social inequality were highlighted.…”
Section: Discussionsupporting
confidence: 72%
“…(7) The validity of this instrument is documented for the care of several types of patients. (8)(9)(10) Compared with usual care, targeted nursing interventions based on the INTERMED scores resulted in improvements in quality of life, at the time of admission and discharge in patients in general practice and in elderly patients requiring interdisciplinary care. (6,(8)(9)(10)(11) Assuming the importance of providing comprehensive care to the hospitalized elderly, this study aims to investigate biopsychosocial aspects of hospitalized elderly, and aspects of the health system, and to classify their degree of care complexity.…”
Section: Introductionmentioning
confidence: 99%
“…These interventions may have modified patient beliefs or their intent to continue, or both. Studies of collaborative care or educational interventions indicate that the provision of educational or supportive interventions that can address topics such as what to do about side effects or the time expected to reach remission may be useful in improving adherence or persistence in taking medications as well as outcomes [4, 6,43,44,45,46]. Personalized responses to each patient’s own expressed concerns may be even more useful in retaining less committed, at-risk patients in treatment for a sufficient time to maximize the chances of reaching and sustaining remission with this often chronic or recurrent illness.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, we have applied this intervention to a sample of 247 high-risk patients recruited at a rheumatology department and a diabetes outpatient clinic, and found that it was successful in reducing the prevalence of major depression, as compared with usual care. 21 Because a substantial proportion of the randomized sample did not suffer from major depression at baseline, we had the opportunity to determine whether the intervention was also capable of preventing incident major depression, and because so few studies have actually looked at this possibility, we performed this subgroup analysis in the present study.…”
Section: Prevention Of Major Depression In Complexmentioning
confidence: 99%